2016
DOI: 10.1002/2016wr018808
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of thermal methods and seepage meters to efficiently locate, quantify, and monitor focused groundwater discharge to a sand‐bed stream

Abstract: Quantifying flow of groundwater through streambeds often is difficult due to the complexity of aquifer‐scale heterogeneity combined with local‐scale hyporheic exchange. We used fiber‐optic distributed temperature sensing (FO‐DTS), seepage meters, and vertical temperature profiling to locate, quantify, and monitor areas of focused groundwater discharge in a geomorphically simple sand‐bed stream. This combined approach allowed us to rapidly focus efforts at locations where prodigious amounts of groundwater disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 64 publications
7
81
3
Order By: Relevance
“…Because shallow hyporheic flow paths in coarse-grained sediments are primarily horizontal and temperature-profile methods assume primarily vertical flow, it should not be surprising that data might be difficult to interpret. Other studies in finer sandbed streams have obtained conclusive and consistent results using these methods (Rosenberry et al, 2016;Hatch et al, 2010). Excluding the questionable temperature-based data in Table 2, when all other location-specific data are aggregated over an entire M or N reach, the conclusion is consistent; greater groundwater discharge occurs at M than at N reaches.…”
Section: Methods Comparisonmentioning
confidence: 54%
“…Because shallow hyporheic flow paths in coarse-grained sediments are primarily horizontal and temperature-profile methods assume primarily vertical flow, it should not be surprising that data might be difficult to interpret. Other studies in finer sandbed streams have obtained conclusive and consistent results using these methods (Rosenberry et al, 2016;Hatch et al, 2010). Excluding the questionable temperature-based data in Table 2, when all other location-specific data are aggregated over an entire M or N reach, the conclusion is consistent; greater groundwater discharge occurs at M than at N reaches.…”
Section: Methods Comparisonmentioning
confidence: 54%
“…The pore‐scale numerical simulations of Liu and Kitanidis () illustrated a need to conduct experiments regarding less‐mobile parameters over a range of flow velocities. Accordingly, our experiments include controlled lakebed injections over a range of downward flux conditions similar to those observed in nearby flow‐through kettle lakes and sand‐and‐gravel‐bed rivers (Rosenberry et al, , ). Preliminary experimentation at Snake Pond in June 2016 using a DDPA at a fixed injection flux indicated that the experimental shoreline sediments have an average hydraulic conductivity of 10 m/day.…”
Section: Methodsmentioning
confidence: 99%
“…DRIPs can influence stream temperature, nutrient availability, and redox conditions in headwater systems (Crawford et al, 2017;Lowry, Walker, Hunt, & Anderson, 2007) and act as biogeochemical hotspots or control points that have a disproportionally large impact on stream water quality (Bernhardt et al, 2017;McClain et al, 2003). DRIPs are important for shaping stream ecosystems and thus progress has been made on detecting their locations along stream networks using topographic and thermal approaches (Kuglerová et al, 2014;Leach, Lidberg, Kuglerová, Ågren, & Laudon, 2017;Rosenberry, Briggs, Delin, & Hare, 2016). Nevertheless, the seasonal dynamics of DRIPs have not been fully comprehended.…”
Section: Introductionmentioning
confidence: 99%